Acidic Character and Catalytic Activity of Sulpho-Functionalized Porous Silica with an Ordered Structure - Akihiko Matsumoto; Fei-Yee Yeoh; Shunsuke Fujihara; Kazuo Tsutsumi; Toshihide Baba (Adsorption Science & Technology)
Microporous organosilica incorporating various amounts of sulpho groups (MS-SO 3 H) was prepared by hydrolysis and the co-condensation of tetramethoxysilane (TMOS) and mercaptopropyl trimethoxysilane (MPTMS), followed by oxidation of the thiol group. The resulting microporous silica had a regular porous structure similar to that of the mesoporous silica MCM-41, as shown by X-ray diffraction and nitrogen adsorption measurements. Ammonia adsorption microcalorimetry indicated that a large number of sulpho groups were successfully incorporated into the microporous silica framework. The sulpho group-incorporating microporous silica (MS-SO 3 H) exhibited catalytic activity towards the isomerization of but-1-ene to cis- and trans -but-2-ene via an acid catalysis mechanism.